Androgens Increase Persistence But Do Not Affect Neophobia in a Problem‐Solving Context in a Songbird. (19th January 2015) - Németh, Zoltán; Adams, Ryan H.; Ramenofsky, Marilyn; Koenig, W.
Abstract Gonadal steroid hormones enhance cognitive performance, particularly spatial and vocal learning, in mammals and birds. However, it is unknown whether problem‐solving ability is similarly regulated. We propose that androgens, such as testosterone and 5α‐dihydrotestosterone, play a role in mediating problem‐solving behavior as well. As a test, male white‐crowned sparrows (Zonotrichia leucophrys gambelii) were either castrated and administered a blank (Blank‐castrate) or testosterone‐filled implant (T‐castrate) or were sham operated and were exposed to a novel feeder, which they had to open to receive a food reward, in two trials. Testosterone treatment affected neither a neophobic response nor problem‐solving performance. However, T‐castrates were more persistent in manipulating the feeder than Blank‐castrates or Shams. Furthermore, their persistence correlated positively with circulating levels of both testosterone and 5α‐dihydrotestosterone. We suggest that a positive correlation between sex steroids and persistence in foraging and problem‐solving contexts may lead to an adaptive increase in resource acquisition in the breeding season. Given the overall low success on the problem‐solving test, we cannot confidently conclude that androgens do not play a role in mediating problem‐solving behavior. However, unlike in mammals, it seems these hormones do not significantly influence neophobia in foraging contexts in birds.